Providing Resource Information Through Radio Public Service Announcements - Rosanne Fortner (Journal of Applied Communications, 1981)
According to the Broadcasting Yearbook (1980), radio has been at a saturation level in American homes since the early 1960's, yet there is a continued growth in the number of licensed radio stations and the number of radio sets per household.